" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
x - y = 6
x = -y
-2y = 6 / :-2
x= 3
y = -3
b.) y = x + 3
2x + y = 9
y = x+3
3x +3=9 /-3 , :3
x=2
y = 2+ 3 =5
c.) x - 4y = 15
y = 4x
y=4x
x - 16x = 15 / :-15
x = -1
y= 4 * (-1) = -4
e.) -3x = 2y
y = 1 - x
y=1-x
-3x=2 -2x/+2x
y=1-x
-x=2 /:-1
x=-2
y= 1- 2 = -1
f.) 5x + 6y = 8
x = 4y - 1
x=4y -1
20y -5 +6y =8 /+5
x=4y-1
26y = 13 /:26
y = 0,5
x= 2-1 = 1
pozdrawiam ;)
x= -y
x-y=6
x= -y
-y-y=6
x=-y
-2y=6 /:(-2)
y= -3
x= -(-3)
y= -3
x=3
y= -3
b)
y=x+3
2x+y=9
y=x+3
2x+x+3=9
y=x+3
3x=6 /:3
y=x+3
x=2
y=2+3
x=2
x=2
y=5
c)
x-4y=15
y=4x
x-4*4x=15
y=4x
x-16x=15
y=4x
-15x=15 /:(-15)
y=4x
x= -1
y= 4*(-1)
x= -1
y= -4
e)
-3x = 2y
y = 1 - x
-3x=2(1-x)
y=1-x
-3x=2-2x
y=1-x
-x=2 /:(-1)
y=1-x
x= -2
y=1-(-2)
x= -2
y=3
f)
5x + 6y = 8
x = 4y - 1
5(4y-1) +6y=8
x=4y-1
20y-5+6y=8
x=4y-1
26y=13 /:26
x=4y-1
y= 1/2
x= 4* 1/2 -1
x=2-1
y= 1/2
x=1
y= 1/2